The Model of Psychologist Competencies Recommended by the European Federation of Psychologists' Associations - Tarnowski, Adam; Łaszewska, Kamila (Przegląd Psychologiczny, 2025)
Purpose: This paper introduces the newly developed psychologist competency framework recommended by the European Federation of Psychological Associations (EFPA). It is a modification of the concept previously proposed in the US by Rodolfa et al. (2005). The competency system is essential for academic institutions because it defines the graduate’s silhouette from the perspective of practical professional skills and supervisors overseeing the placement of psychology graduates entering the profession. This article argues in favor of incorporating knowledge based on the competency framework model into the content of psychology education at Polish universities to increase the chance of a more precise assessment of the equivalence of education and higher quality of professional psychological services. The difficulties of adapting the EFPA program to the national system of psychology education are also pointed out, and the key challenges and recommendations for the successful adaptation of the EFPA program to the Polish reality are analysed. Theses: Discussion of changes in the framework competence model and their significance. Discuss the stages of training psychologists within the model proposed by the EFPA. Presentation of the division of competences into complementary functional competences (what a psychologist does) and foundational competences (how a psychologist works), and stages of professional development. As a member country of the EFPA, Poland has the opportunity to implement the EFPA model, but adapting it to the national system of training psychologists involves difficulties. Conclusions: The competency framework adopted by EFPA in 2023 defines the objectives of psychological education. It was developed due to many years of work by psychologists affiliated with EFPA, constituting a practical and realistic system for ensuring future psychologists’ education quality. Precise definitions and specific learning outcomes enable an objective and standardised assessment of readiness for independent work, the final stage of five years of study, and a one-year postgraduate internship. Implementing the EFPA model requires the adaptation of numerous aspects of the national education system, changes in the organisation of studies, the course of post-diploma internships, and legal regulations concerning the profession of psychologist.